Enhanced surface activity of SnO2 thin film verified by LM algorithm. (April 2016) - Choudhury, Sandip Paul; Kumari, Navnita; Bhattacharjee, Ayon
Abstract: Impedance studies were conducted on spray deposited Cu doped SnO2 thin films. Rietveld analysis provided evidence of non-existence of any other phase due to doping. Controlled injection of ethanol vapor was done to study the surface activity of these films at different temperatures. The cole–cole plots of ethanol absorbed films to that of unexposed thin films were constructed at different temperatures and compared. The studies reveal that the electron scattering process was homogeneous in nature and the film had a narrow relaxation time. Levenberg–Marquardt algorithm with unweighted function was used for theoretical fitting of the cole–cole plots that revealed the weakening of the Fermi pinning level. Highlights: The theoretical aspects for change in impedance properties were analyzed using LM algorithm. The deposited thin film successfully detected ethanol vapor and was related to the change in the impedance of the system due to grain and bulk boundaries. The surface activity of the film was enhanced and explanation for the same is attempted.